2022
DOI: 10.1111/ecc.13597
|View full text |Cite
|
Sign up to set email alerts
|

Can improving quality of sleep reduce the symptoms of cancer‐related fatigue in adults?: A systematic review

Abstract: Purpose: Cancer-related fatigue (CRF) results in reduced quality of life for cancer patients. The relationship between tiredness and fatigue has been established in cancer patients and has been shown to be reciprocal, meaning the relationship is somewhat 'chicken or the egg' with tiredness influencing fatigue and vice versa. The aim of this study is to determine whether an improvement in sleep quality can ease the symptoms of CRF and whether this can support the theory that CRF symptoms stem from the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Cheung et al (2015) found the decline in brain activity after stimulating the Shenmen acupoint, which is associated with reduced arousal, suggests Shenmen acupoint stimulation may promote sleep. Strong scientific evidence supports that increasing total sleep time reduces the symptoms of fatigue (Dean, 2022; Mantua et al, 2019), which may explain the beneficial effect of Shenmen acupoint selection on fatigue alleviation in patients receiving hemodialysis. However, the question remains regarding the direction of the effect between sleep improvement and fatigue mitigation.…”
Section: Discussionmentioning
confidence: 97%
“…Cheung et al (2015) found the decline in brain activity after stimulating the Shenmen acupoint, which is associated with reduced arousal, suggests Shenmen acupoint stimulation may promote sleep. Strong scientific evidence supports that increasing total sleep time reduces the symptoms of fatigue (Dean, 2022; Mantua et al, 2019), which may explain the beneficial effect of Shenmen acupoint selection on fatigue alleviation in patients receiving hemodialysis. However, the question remains regarding the direction of the effect between sleep improvement and fatigue mitigation.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, a recent systematic review showed that improving sleep quality eased the symptoms of cancer-related fatigue although was unable to determine if sleep quality improvement was the sole factor behind fatigue lessening. 20 Of note, patients who had been overweight before weight loss reported positive impact of weight loss, especially female patients.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, 30–60% of cancer survivors experienced CRF during treatment (Bower, 2014 ), which significantly reduced the quality of daily life (Yang et al, 2019 ) and shortened survival (Quinten et al, 2011 ). Related studies have found that when compared with survivors with low fatigue trajectory, survivors with high fatigue trajectory were more often associated with anxiety, depression and sleep disorders (Bower et al, 2018 ; Dean, 2022 ). Therefore, it is necessary to take appropriate measures and interventions to reduce CRF for cancer survivors.…”
Section: Introductionmentioning
confidence: 99%